Parkinson's Disease Cell Vulnerability and Disease Progression - Jose A. Obeso (Frontiers Research Topics, 2015)
Parkinson's disease is a neurodegenerative disorder that affects 1.5% of the global population over 65 years of age. The hallmark feature of this disease is the degeneration of dopamine neurons in the substantia nigra pars compacta and a consequent striatal dopamine deficiency. The pathogenesis of Parkinson's Disease remains unclear. Despite tremendous growth in recent years in our knowledge of the molecular basis of Parkinson's Disease and the molecular pathways of cell death important questions remain regarding why are substantia nigra cells especially vulnerable, which mechanisms underlie progressive cell loss or what do Lewy bodies or alpha-synuclein reveal about disease progression. Understanding the different vulnerability of the dopaminergic neurons from midbrain regions and the mechanisms whereby pathology becomes widespread are primary objectives of basic and clinical research in Parkinson's Disease. This e-Book discusses the etiopathogenesis of Parkinson's Disease, presenting a series of papers that provide up-to-date, state-of-the-art information on molecular and cellular mechanisms involved in the neurodegeneration process in the disease, the role of activation of functional anatomical organization of the basal ganglia and in particular habitual vs goal directed systems as a factor of neuronal vulnerability, the possibility that Parkinson's Disease coulb be a prion disease and how genetic factors linked to familial and sporadic forms of PD. We hope that this e-Book will stimulate the continuing efforts to understand the cell and physiological mechanisms underlying the origin of Parkinson's Disease.